Antimafia and womens movement. Key players, culture and languages (Rivista di Studi e Ricerche sulla criminalità organizzata, 2016)
The essay analyses the role of women in the antimafia movements, starting from their presence - conspicuous and important - inside the Fasci of Workers in Sicily in the late 19th century until the experiences of the Comitato dei Lenzuoli and the Associazione donne per il digiuno born in Palermo after the massacres of Capaci and via D’Amelio, where the figures of women had a first focus role experimenting with alternative and effective ways of expression and of social activism. The approach chosen for the analysis intertwines the studies about mafia as a violent and totalitarian system with the relationship between the sexes, intended as contrast between powers, where a noticeable importance is held by the symbolic dimension. Observing, from a diachronic perspective, the contexts and the associated forms of fighting mafia, the presence of women, even though numerous at times, struggles to find long-lasting structured forms and rather amounts to a place for the occasional expression of original communicational forms and fighting means which differ for their harmony with everyday life, the sphere of subjectivity and the biographical dimension.Keywords: women movements; mafia/antimafia; forms of communication; gender studies; violence